2016
DOI: 10.1093/mmy/myw059
|View full text |Cite
|
Sign up to set email alerts
|

The cytotoxic T cells may contribute to thein situimmune response in Jorge Lobo's Disease human lesions

Abstract: Jorge Lobo's Disease (JLD) is a cutaneous chronic granulomatous disease caused by the pathogenic fungus Lacazia loboi. It is characterized by a granulomatous reaction with multinucleated giant cells and high number of fungal cells. In order to contribute to the comprehension of immune mechanisms in JLD human lesions, we studied the cytotoxic immune response, focusing on TCD8+ and NK cells, and granzyme B. Forty skin biopsies of lower limbs were selected and an immunohistochemistry protocol was developed to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…In accordance, Alexandre and coworks showed that the cytotoxic immune response was a mechanism to control Lacazia loboi infection. They suggested that CD8 + T cells could play a role in the elimination of the fungus (Alexandre et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance, Alexandre and coworks showed that the cytotoxic immune response was a mechanism to control Lacazia loboi infection. They suggested that CD8 + T cells could play a role in the elimination of the fungus (Alexandre et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxic function of CD8+ T cells was evidenced based on the detection of perforin and granzyme B and a role in the in situ immune response to eliminate the fungus was suggested. Similarly, by studying the cytotoxic cellular response in such lesions, we highlight and suggest an important role of these cytotoxic elements 7 .…”
Section: Introductionmentioning
confidence: 95%
“…Concluindo-se que, embora as células T CD4+ sejam essenciais para a defesa do hospedeiro na DJL, as células T CD8+ poderiam desempenhar um papel na eliminação do fungo (Alexandre et al, 2017). No que se refere à CBM, as condições imunológicas do hospedeiro, a virulência, viabilidade e quantidade de parasita são fatores determinantes do curso da infecção.…”
Section: Vilaniunclassified